2015
DOI: 10.3390/met5010192
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum Die Casting Process and Simulation for Manufacturing 0.8 mm-Thick Aluminum Plate with Four Maze Shapes

Abstract: Using vacuum die casting, 0.8 mm-thick plates in complicated shapes are manufactured with the highly castable aluminum alloy Silafont-36 (AlSi9MgMn). The sizes and shapes of the cavities, made of thin plates, feature four different mazes. To investigate formability and mechanical properties by shot condition, a total of six parameters (melt temperatures of 730 °C and 710 °C; plunger speeds of 3.0 m/s and 2.5 m/s; vacuum pressure of 250 mbar and no vacuum) are varied in experiments, and corresponding simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
5
0
1
Order By: Relevance
“…Jin and Kang used MAGMA S/W to design mold for a thin plate with 0.8 mm thickness and to predict the casting defects. They showed that simulation results were completely consistent with experimental results [15][16][17]. The manufacturing process conditions of the carrier housing were derived using a mold structure designed in a computer aided engineering (CAE) environment.…”
Section: Introductionmentioning
confidence: 56%
“…Jin and Kang used MAGMA S/W to design mold for a thin plate with 0.8 mm thickness and to predict the casting defects. They showed that simulation results were completely consistent with experimental results [15][16][17]. The manufacturing process conditions of the carrier housing were derived using a mold structure designed in a computer aided engineering (CAE) environment.…”
Section: Introductionmentioning
confidence: 56%
“…The momentum conservation and continuity equations can describe this process. The process of heat exchange between liquid metal and mold can be described by energy conservation and Fourier's law [9] .…”
Section: Mode Flow Analysismentioning
confidence: 99%
“…The process follows the law of mass, energy, and momentum conservation. Assuming that the liquid metal is an incompressible fluid and ignores the influence of turbulence, the process can be described by the volume function, continuity, energy conservation equation, and the dynamic theory of the liquid particle solidification process [9][10] . In this paper, the MAGMA software is used to analyze the mode flow [11] .…”
Section: Mode Flow Analysismentioning
confidence: 99%
“…Accordingly, several studies have been performed in order to develop more suitable and costeffective materials for the fabrication of BPPs, such as metals and composites [9]. Further, the adoption of metallic materials allows for the application of other manufacturing techniques, including stamping [10], hydroforming [11], rubber pad forming [12], micro-electrical discharge machining (μEDM) [13], electrochemical micro-machining [14], and vacuum die casting [15]. Among the metals candidates for BPPs, stainless steels, Ni-based alloys, Ti-based alloys, and Albased alloys have been considered for PEM fuel cells [6].…”
Section: Introductionmentioning
confidence: 99%